The Effect of a Passing Training Program on Basketball Shooting Accuracy Among Students at SMPN 2 South Bengkulu - Farhan Ilham Apriyanto; Roni Syaputra; Desrio Windoro (Educative Sportive, 2026)
This study aims to determine the effect of passing drills on basketball shooting accuracy among students in the extracurricular basketball program at SMP Negeri 2 Bengkulu Selatan. The research method used was an experimental method with a pre-experimental design employing a one-group pretest-posttest design. The population for this study consisted of all 20 students in the basketball extracurricular program at SMP Negeri 2 Bengkulu Selatan. The research sample consisted of 15 students. The research instrument used a 5-point shooting test. The training program was conducted for 1 month and 2 weeks, with training sessions held 3 times a week, for a total of 15 sessions. Based on the results of the hypothesis test using the t-test, the calculated t-value of 11.215 was greater than the critical t-value of 2.145 (11.215 > 2.145). Thus, H₀ was rejected and H₁ was accepted. The results of the study indicate that there was a significant improvement of 90.63% in shooting accuracy among students in the extracurricular program at SMP Negeri 2 Bengkulu Selatan as a result of passing drills.